2018
DOI: 10.3390/ijms19103233
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Follicular T Helper Cells in Multiple Sclerosis and Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis (MS) is an autoimmune disorder where both T cells and B cells are implicated in pathology. However, it remains unclear how these two distinct populations cooperate to drive disease. There is ample evidence from studies in both MS patients and mouse models that Th17, B cells, and follicular T helper (TFH) cells contribute to disease. This review article describes the literature that identifies mechanisms by which Th17, TFH, and B cells cooperatively drive disease activity in MS and experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 113 publications
0
19
0
Order By: Relevance
“…LTo cells also begin to express intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 in order to aid in immune cell retention upon entry. Finally, LTo cells will differentiate into FDCs, fibroblastic reticular cells (FRCs), and marginal reticular cells, which comprise the stromal reticular network ( 89 , 91 , 92 ).…”
Section: Ectopic Lymphoid Follicles In Multiple Sclerosis: Centers Fomentioning
confidence: 99%
See 2 more Smart Citations
“…LTo cells also begin to express intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 in order to aid in immune cell retention upon entry. Finally, LTo cells will differentiate into FDCs, fibroblastic reticular cells (FRCs), and marginal reticular cells, which comprise the stromal reticular network ( 89 , 91 , 92 ).…”
Section: Ectopic Lymphoid Follicles In Multiple Sclerosis: Centers Fomentioning
confidence: 99%
“…Partially due to their formation being initiated by inflammation, eLFs can form and dissipate quickly. As a direct consequence of this transient nature, eLFs can display significant organizational and cellular heterogeneity ranging from small and disorganized aggregates of B and T cells to highly organized structures containing compartmentalized T and B cell zones, HEVs, FDCs, and a developed stromal reticular network ( 10 , 11 , 80 , 90 , 91 ). It is important to note, however, that once the reticular network has formed and an eLF has reached an advanced state of maturation, eLFs become fairly stable and are less likely to dissipate ( 94 ).…”
Section: Ectopic Lymphoid Follicles In Multiple Sclerosis: Centers Fomentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro assays showed that the B cells from MS patients display the capacity of coordinating Th17 riposte against neuro-antigens (30). As a result, in 2018 Quinn and Axtell described an 'inflammatory axis' consisting of Th17 cells, B cells and follicular Th cells (31). Th17 cells through their implication in the formation of the subpial follicles, have a contributory role in the underlying subpial grey matter pathology (4).…”
Section: Th17 Cells and Ectopic Lymphoid-like Structuresmentioning
confidence: 99%
“…To date, the experimental autoimmune encephalomyelitis (EAE) animal model best mimics the clinical and pathological hallmarks of multiple sclerosis and can offer the essential predictive guide for clinical therapeutic application (Miller and Karpus, 2007; Quinn and Axtell, 2018). Significantly elevated concentrations of acrolein, an α, α-unsaturated aldehyde and a reactive product of lipid peroxidation, has been found after rat spinal cord contusion injury.…”
Section: Introductionmentioning
confidence: 99%